Age Hardening and Microstructure of ZA84 Magnesium Alloy with the Combined Addition of Cr and Bi. Issue 1 (January 2018) - Jie, Ye; Xiaoping, Lin; Yun, Dong; Fei, Teng; Guifang, Sun; Jie, Han
Abstract: The age hardening and microstructure of ZA84 magnesium alloy with the combined addition of Cr and Bi was studied by SEM and HRTEM. The results show that a trace amount of Cr and Bi has a significant enhancement effect on the hardness of aging. When the ZA84-0.2Cr-0.5Bi alloy was aged at 160 °C, during the early aging period, the matrix has serious lattice distortion and a large number of crystal defects. The microstructure at the peak aging consists of a large number of rod-like or blocky β′1 -MgZn2 phases and granular Bi2 Mg3 phases, and the peak hardness HV value is 924.8 MPa. When ageing proceed, the precipitates coarsening results in the hardness value reduction.